2021
DOI: 10.1111/ene.14716
|View full text |Cite
|
Sign up to set email alerts
|

Increased muscle echointensity correlates with clinical disability and muscle strength in chronic inflammatory demyelinating polyneuropathy

Abstract: Background and purpose We evaluated muscle echointensity as a marker for secondary axonal damage in patients with chronic inflammatory demyelinating polyneuropathy (CIDP) using ultrasonography. Findings were correlated with clinical disability and muscular strength. Methods Eighty patients with CIDP (40 with typical and 40 with atypical CIDP) were examined clinically, including assessment of Medical Research Council (MRC) sum score and Inflammatory Neuropathy Cause and Treatment Overall Disability Sum Score (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
(22 reference statements)
0
7
0
2
Order By: Relevance
“…Second, evidence of PSA on electromyography in CIDP has been associated with a worse long‐term outcome [11]. Third, increased muscle echointensity, reflecting fibrosis and fatty infiltration due to secondary axonal damage, correlated with muscular strength and disability in CIDP patients [29].…”
Section: Discussionmentioning
confidence: 99%
“…Second, evidence of PSA on electromyography in CIDP has been associated with a worse long‐term outcome [11]. Third, increased muscle echointensity, reflecting fibrosis and fatty infiltration due to secondary axonal damage, correlated with muscular strength and disability in CIDP patients [29].…”
Section: Discussionmentioning
confidence: 99%
“…13,14 However, only a few studies have investigated the MUS findings of demyelinating neuropathies. 5,15 Chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) is a common demyelinating neuropathy. Our previous study and the study by Fisse et al 5 reported that morphologic changes in MUS reflect secondary axonal degeneration in the disease.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Recently, several studies have shown that MUS can be a promising biomarker for neuromuscular diseases. [3][4][5][6] The utility of quantitative MUS evaluation of EI and MT has been reported in various axonal degenerative diseases like motor neuron diseases, brachial plexopathies, and several axonal neuropathies. 2,4,7,8 In amyotrophic lateral sclerosis (ALS), e.g., EI and MT have a fair correlation with muscle weakness and electrophysiological findings.…”
Section: Discussionmentioning
confidence: 99%
“…Dies tritt z. B. bei Motoneuronerkrankungen und schweren chronischen Radikulopathien auf, kann aber auch bei Immunneuropathien wie der CIDP infolge eines sekundären axonalen Schadens erscheinen [35]. Das Muster der Muskelbeteiligung im Ultraschall kann verwendet werden, um die zugrundeliegende neurogene Schädigung z.…”
Section: Muskelultraschall Bei Polyneuropathienunclassified
“…In der dynamischen Untersuchung können neurogene Faszikulationen bei Polyneuropathien im Ultraschall beobachtet werden, deren Bedeutung klinisch noch nicht geklärt ist. Diese könnten jedoch in longitudinalen Beobachtungen einen prognostischen Krankheitswert haben [35].…”
Section: Muskelultraschall Bei Polyneuropathienunclassified